Ancient Mesopotamia at the dawn of civilization : the evolution of an urban landscape - Algaze, Guillermo, 1954- (University of Chicago Press, 2008)
The alluvial lowlands of the Tigris and Euphrates rivers in southern Mesopotamia are widely known as the "cradle of civilization" owing to the scale of the processes of urbanization that took place in the area by the second half of the fourth millennium BC. In Ancient Mesopotamia at the Dawn of Civilization, Guillermo Algaze draws on the work of modern economic geographers to explore how the unique river-based ecology and geography of the Tigris-Euphrates alluvium impacted the development of urban civilization in southern Mesopotamia. He argues that these natural conditions granted southern po